Numerical investigation of thermo-mechanical behaviour and microstructure evolution of a nickel alloy workpiece during its upsetting - Rogovoy, Anatoliy Alekseyevich; Salikhova, Nelli Kamilevna (Computational Continuum Mechanics, 2021)
The use of science-based technologies in commercial production makes it possible to obtain high-quality, competitive finished products. The development of new techniques or optimization of existing technological processes involving the in-depth experimental research requires large time and material costs. In this regard, numerical simulation of the technological process under study can be used as an alternative to a physical experiment. The results obtained by numerical methods will make it possible to substantiate the most appropriate regime of billet deformation, providing the required changes in the structure of the material. This paper considers a specific technological process of hot forming of massive billet consisting of two stages: air cooling of the billet while transporting it from the furnace to deforming tools and forming operation - free upsetting of a billet with the aid of a moving upper flat plate and a stationary cutting lower plate. Computer simulation of upsetting of a large billet with the aim to define a change in its shape, temperature distribution over the surface and throughout the billet, and deformation inhomogeneity arising in the process of got forming was carried out using the Deform-2D/3D software package. The initial temperature distribution of material during pressure forming is determined by modeling air cooling of the billet for 45 seconds during its transportation from the furnace to the deforming equipment. For the obtained inhomogeneous temperature distribution, the calculations were performed to evaluate the force required for billet upsetting to the technology specified average diameter of about 1060 mm at the velocity of the die movement of 100 mm/s. Thee Johnson-Mehl-Avrami-Kolmogorov (JMAK) model was used to investigate the evolution of the microstructure (average grain size and recrystallized volume fraction) of the Waspalloy nickel alloy generated as a result of dynamic recrystallization in the process of hot forming of a billet at the strain rate of 100 mm/s.